TRANSMEDIA EDUCATION: MASCULINITY IN TIKTOK WITHIN TRADITIONAL DANCE - Syfa Amelia; Farah Fajriyah; Dhiya Sahara Ulfa; Denis Hida Lutfiani Stefani (Universitas 17 Agustus 1945 Semarang, 2023)
The advent of internet and the proliferation of social media change the way teachers and students consume and create educational learning content, such as Java traditional dance. Men traditional dancers get bullied because they are considered less masculine where it happens in the education sector, school or dance studio. TikTok in the transmedia era known as an entertainment, expression and education space. TikTok’s content creators (Abing, Fahrul, BM) actively post to preserve culture. This research examines TikTok as an education and expression’s medium, challenges the gender dichotomy in Indonesia’s new masculinity. This research uses the case study, interview art activists, finding audience's reception from the comments, documents, relevant preliminary research. The results show male traditional dancers use TikTok to express themselves and preserve local culture. TikTok’s existence also shifts masculinity where it is not only interpreted as a form of virility, but also contains tenderness and femininity in traditional dance.